Proteome of the phytopathogen Xanthomonas citri subsp citri: a global expression profile - Soares, Marcia R.; Facincani, Agda P. [UNESP]; Ferreira, Rafael M. [UNESP]; Moreira, Leandro M.; de Oliveira, Julio C. F.; Ferro, Jesus A. [UNESP]; Ferro, Maria I. T. [UNESP]; Meneghini, Rogerio; Gozzo, Fabio C. (Biomed Central Ltd., 2010)
Background: Citrus canker is a disease caused by Xantomonas citri subsp. citri (Xac), and has emerged as one of the major threats to the worldwide citrus crop because it affects all commercial citrus varieties, decreases the production and quality of the fruits and can spread rapidly in citrus growing areas. In this work, the first proteome of Xac was analyzed using two methodologies, two-dimensional liquid chromatography (2D LC) and tandem mass spectrometry (MS/MS).Results: In order to gain insight into the metabolism of Xac, cells were grown on two different media (NB - Nutrient Broth and TSE - Tryptone Sucrose broth enriched with glutamic acid), and proteins were proteolyzed with trypsin and examined by 2D LC-MS/MS. Approximately 39% of all predicted proteins by annotation of Xac were identified with their component peptides unambiguously assigned to tandem mass spectra. The proteins, about 1,100, were distributed in all annotated functional categories.Conclusions: This is the first proteomic reference map for the most aggressive strain of Xanthomonas pathogen of all orange varieties. The compilation of metabolic pathways involved with bacterial growth showed that Xac expresses a complete central and intermediary metabolism, replication, transcription and translation machineries and regulation factors, distinct membrane transporters (ABC, MFS and pumps) and receptors (MCP, TonB dependent and metabolites acquisition), two-component systems (sensor and regulatory components) and response regulators. These data corroborate the growth curve in vitro and are the first reports indicating that many of these genome annotated genes are translated into operative in Xac. This proteomic analysis also provided information regarding the influence of culture medium on growth and protein expression of Xac.